Effective Parking Management System Based On Search and Occupy Algorithem Using Arduino UNO - Chettri, Robin; Rasaily, Deepak; Chhinal, Shyam; Rai, Bikash; Sharma, Gulsan; V, Greacy (International Journal of Computer Sciences and Engineering, 2020)
This paper describes an approach to overcome a situation of monitoring and managing a parking area using arduino based effective parking management system. With the rapid increasing of cars the need to find available parking space in the most efficient manner, to avoid traffic congestion in a parking area become difficult. This paper aimed at develop a effective car parking management system that is more cost effective and user friendly existing system, confusion free and easy parking. The main purpose of effective parking system is to reduce time to locate the parking areas, hence it reduce fuel consumption. The system counts the number of cars in any parking places and checks if there’s any vacancy. The first phase aimed at making cars datable in the parking lot through the use of sensor used for searching the unoccupied parking facility. The discussed system will be able to reduce the problems which are arising due to unavailability of a reliable, efficient and modern parking system, while the economic analysis technique will help in analyzing the project feasibility.